2008
DOI: 10.1016/j.hrthm.2008.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Overrepresentation of the proarrhythmic, sudden death predisposing sodium channel polymorphism S1103Y in a population-based cohort of African-American sudden infant death syndrome

Abstract: Background-The S1103Y-SCN5A polymorphism has been implicated as a pro-arrhythmic, sudden death predisposing risk factor in African Americans including one postmortem investigation of African American infants with sudden infant death syndrome (SIDS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 23 publications
4
44
1
Order By: Relevance
“…Plant et al found an overrepresentation of this mutation in a cohort of 133 SIDS cases, suggesting a 24-fold increased risk for SIDS in infants with the YY genotype [49], while another study found that 22.5% of the investigated SIDS cases had the heterozygous SY genotype [52]. The authors showed that Y1103 channels demonstrated abnormal function when subjected to low intracellular pH, in comparison to S1103 channels [49].…”
Section: Cardiac Arrhythmiamentioning
confidence: 97%
See 2 more Smart Citations
“…Plant et al found an overrepresentation of this mutation in a cohort of 133 SIDS cases, suggesting a 24-fold increased risk for SIDS in infants with the YY genotype [49], while another study found that 22.5% of the investigated SIDS cases had the heterozygous SY genotype [52]. The authors showed that Y1103 channels demonstrated abnormal function when subjected to low intracellular pH, in comparison to S1103 channels [49].…”
Section: Cardiac Arrhythmiamentioning
confidence: 97%
“…The SCN5A S1103Y mutation has been reported to be of special importance in African-American SIDS cases [49,52]. Plant et al found an overrepresentation of this mutation in a cohort of 133 SIDS cases, suggesting a 24-fold increased risk for SIDS in infants with the YY genotype [49], while another study found that 22.5% of the investigated SIDS cases had the heterozygous SY genotype [52].…”
Section: Cardiac Arrhythmiamentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] In this regard, although the risk of African American race may reflect a particularly high burden of extrinsic risk factors, eg, bed-sharing, 14,15 in this population, we chose to place emphasis on the role of possible (intrinsic) genetic polymorphisms that may increase risk relative to race itself. 16,17 Information about every risk factor was not available in every case.…”
Section: Figurementioning
confidence: 99%
“…78,79 It was also found to be enriched in a set of SIDS cases of African American descent. 80,81 This variant is thought to promote arrhythmia susceptibility during exposure to extrinsic factors such as QTprolonging medication or acquired cardiac disease, in line with a multihit pathogenesis for cardiac arrhythmia. Collaborative studies led by the groups of Professors Ackerman and Makielski show the biophysical consequences of this polymorphism.…”
Section: Common Variants In the Scn5a Coding Regionmentioning
confidence: 99%